Mathematical and Finite Element Modeling of Micro-Modification for Marine Gear - Xiongxi Wu; Qifeng Gao; Zesong Li (International Journal of Rotating Machinery)
Based on the computer simulation technique, this paper used the professional gear design software MASTA and finite element software ANSYS combined with the method of gear micro-modification to redesign the gear profile and eventually realized the optimization design of gear micro-modification. Then the gear transmission model of one-level reducer was established to simulate and analyze the contact equivalent stress, transmission error, and meshing impact before and after gear modification. By comparing the simulations results it is found that gear micro-modification can lower meshing impact load, reduce the vibration strength, make gear transmission steady, and improve the gear bearing capacity. By comparing the transmission error curves and meshing impact load curves before and after gear micro-modification, this helps to understand the effects of gear micro-modification on the gear transmission and provides basis references for the future redesign of the marine gears with high strength and long service life.